2016
DOI: 10.1111/ijlh.12470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of parameters obtained from the Sysmex XN‐2000 for predicting the recovery of the absolute neutrophil count and platelets after hematopoietic stem cell transplantation

Abstract: There is a systematic pattern where a rise in most of the studied parameters can be observed in most patients before ANC/platelet recovery. However, the interindividual variation between the time of rise of these parameters and ANC/platelet recovery is large, and therefore, using these parameters to predict recovery in the individual patient is probably not meaningful in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Percentage of IPF (IPF%) values correlate well with RP% values obtained by thiazole orange staining (8). It has been demonstrated that IPF% values, especially when measured using the XN series, as well as RP% values, are useful to determine platelet turnover in thrombocytopenic disorders, and for predicting platelet recovery after stem cell transplantation (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Percentage of IPF (IPF%) values correlate well with RP% values obtained by thiazole orange staining (8). It has been demonstrated that IPF% values, especially when measured using the XN series, as well as RP% values, are useful to determine platelet turnover in thrombocytopenic disorders, and for predicting platelet recovery after stem cell transplantation (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…the time between first rise of the prediction parameter and platelet recovery) of 4.0, 4.5 and 5.0 days for PDW, MPV and P-LCR, respectively, was also significantly longer than for IPF (1.5 days) [74]. However, the authors noted a large inter-individual variation between the rise of the aforementioned parameters and platelet recovery and concluded, that IPF was not clinically meaningful to predict platelet recovery to >20.0 × 10 9 /L, which is the critical decision-making level for platelet transfusion [74]. Although earlier studies suggested that reticulated platelets may be used as a parameter to optimize transfusion policies for platelet concentrates in patients undergoing intensive chemotherapy or HPSCT [20,55,71,75], appropriate prospective trials have not been set-up yet.…”
Section: Recovery Of Thrombopoiesis After Cytostatic Therapy and Tranmentioning
confidence: 83%
“…The median time benefit (i.e. the time between first rise of the prediction parameter and platelet recovery) of 4.0, 4.5 and 5.0 days for PDW, MPV and P-LCR, respectively, was also significantly longer than for IPF (1.5 days) [74]. However, the authors noted a large inter-individual variation between the rise of the aforementioned parameters and platelet recovery and concluded, that IPF was not clinically meaningful to predict platelet recovery to >20.0 × 10 9 /L, which is the critical decision-making level for platelet transfusion [74].…”
Section: Recovery Of Thrombopoiesis After Cytostatic Therapy and Tranmentioning
confidence: 92%
See 2 more Smart Citations